2020
DOI: 10.3390/coatings10090897
|View full text |Cite
|
Sign up to set email alerts
|

Tribology of 2D Nanomaterials: A Review

Abstract: The exfoliation of graphene has opened a new frontier in material science with a focus on 2D materials. The unique thermal, physical and chemical properties of these materials have made them one of the choicest candidates in novel mechanical and nano-electronic devices. Notably, 2D materials such as graphene, MoS2, WS2, h-BN and black phosphorus have shown outstanding lowest frictional coefficients and wear rates, making them attractive materials for high-performance nano-lubricants and lubricating application… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 150 publications
(190 reference statements)
0
38
0
Order By: Relevance
“…The relative movement of the contact surfaces provides shear stress for the as-prepared Ti 3 C 2 T x . In addition, the easy relative slip between the layers of the interlayer in the multilayer 2D DDP-Ti 3 C 2 T x nanosheets forms a sliding system with frictional contact. , The friction in the sliding system is much lower, resulting in effective lubrication. Furthermore, Ti 3 C 2 T x nanosheets can be easily destroyed under the condition of higher loads, forming smaller nanofragments, and the damaged Ti 3 C 2 T x fragments fill into the depression of the friction pair, which makes the friction pair surface smoother, reduces the roughness of the contact surface, and decreases wear volume .…”
Section: Resultsmentioning
confidence: 99%
“…The relative movement of the contact surfaces provides shear stress for the as-prepared Ti 3 C 2 T x . In addition, the easy relative slip between the layers of the interlayer in the multilayer 2D DDP-Ti 3 C 2 T x nanosheets forms a sliding system with frictional contact. , The friction in the sliding system is much lower, resulting in effective lubrication. Furthermore, Ti 3 C 2 T x nanosheets can be easily destroyed under the condition of higher loads, forming smaller nanofragments, and the damaged Ti 3 C 2 T x fragments fill into the depression of the friction pair, which makes the friction pair surface smoother, reduces the roughness of the contact surface, and decreases wear volume .…”
Section: Resultsmentioning
confidence: 99%
“…where N [rev/s] is the rotation speed of the inner cylinder (rotor), and M [N‱m] is the torque applied to the rotor. Equation ( 12) follows from Equation (8) and ω i = 2πN, while Equation ( 13) follows from the general torque formula. The inner and outer radiuses of the measuring gap were r i = 14.36 mm and r e = 14.46 mm, and the length of the measuring gap L = 15.00 mm has to be corrected by c L = 1.104 to account for the gap end effects.…”
Section: Model Of the Non-isothermal Couette Flowmentioning
confidence: 99%
“…MoS 2 is also characterized by good thermal stability and corrosion resistance. Due to its unique properties, MoS 2 finds various applications on the friction material market, such as solid lubricants and additives of lubricating oils and greases [6][7][8]. In order to enhance the tribological and rheological behavior, multiple types of MoS 2 materials have recently appeared.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al (2017) found that the wear resistance decreasing at higher RH conditions was found for the MoS 2 and MoS 2 /Ti composite coatings ( Figure 1E ). It has been widely accepted that the lubricity loss of MoS 2 in humid environments is mainly attributed to the chemical oxidation of MoS 2 layers activated by water vapor, which results in the formation of MoO 3 with worse frictional profiles ( Windom et al, 2011 ; Curry et al, 2017 ; Uzoma et al, 2020 ). Other studies focus on the enhanced molecular interactions of water with the layers as the fundamental mechanism behind the observed loss of MoS 2 lubricant properties ( Levita et al, 2016 ; Levita and Righi, 2017 ).…”
Section: Two-dimensional Materialsmentioning
confidence: 99%